The Influence Of Customer Perceived Value And Customer Trust On Customer Loyalty In J&T Delivery Services Bengkalis - Mira Ernilawati; Hutomo Atman Maulana (Politeknik Negeri Bengkalis, 2022)
The development of the delivery service business is quite rapid with the presence of various shipping companies that are tough competitors for other shipping companies. This study aims to determine the effect of customer perceived value and customer trust on customer loyalty on J&T delivery services in Bengkalis. The type of research used is associative research with a quantitative approach. The variables in this study include the value of customer perception, customer trust and customer loyalty. The population of this research is people who use J&T delivery services in Bengkalis. The sample used in this study was 100 respondents who were taken using purposive sampling technique and the data collection method was using a questionnaire. The data analysis used is descriptive analysis, classical assumptions, multiple linear regression, T test, and F test. The results of this study indicate that the variable perceived value by customers partially has a positive and significant effect on customer loyalty, customer trust also has a positive and significant impact. significant to customer loyalty. And simultaneously the two independent variables have a significant effect on customer loyalty.